Islamic Spiritual Mental Development Management To Improve The Religius Character Of The Warrior At MAKODAM III/ Siliwangi - Muhidin; Mahmud; Ajid Thohir; Mohamad Erihadiana (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
This study examines the management of Islamic spiritual mental development in improving the religious character of soldiers at the Headquarters of the Military Regional Command (Makodam) III/Siliwangi. The research is grounded in the understanding that soldiers’ mental resilience, discipline, and moral integrity are essential determinants of military professionalism and operational readiness. Despite established traditions of discipline within the Indonesian Army (TNI–AD), various challenges related to religious commitment, moral behavior, and psychological resilience persist, necessitating systematic spiritual development. This study employs a qualitative research approach to explore the processes of planning, organizing, implementation, supervision, and evaluation of Islamic spiritual development programs, as well as the supporting and inhibiting factors influencing their effectiveness. Data were collected through observations, in-depth interviews with key informants, and document analysis, and were analyzed using the Miles and Huberman interactive model to ensure credibility and analytical rigor. The findings indicate that Islamic spiritual mental development at Kodam III/Siliwangi is managed in a structured and integrated manner, guided by official TNI–AD policies and adapted to local operational conditions. Program implementation includes routine religious guidance, congregational worship, Qur’anic studies, counseling, and family-oriented spiritual activities, supported by strong leadership commitment and an institutional religious culture. The program has contributed to increased worship discipline, improved moral conduct, strengthened integrity, and a reduction in disciplinary violations among soldiers. However, its implementation faces constraints related to operational demands, limited personnel, and scheduling flexibility. Overall, the study concludes that effective integration of management functions, aligned with Islamic education management principles and the CIPP evaluation model, plays a significant role in strengthening soldiers’ religious character within a military context.